Consumer Satisfaction Within the Framework of Sharia: Study on the Influence of QRIS in Sanana District - Gorontalo, Rifani; Takim, Akbar; Kemhay, Ichsan Fachri (Civiliza Publishing, Indonesia., 2025)
One of the important transformations is the digitalization of payment systems through cashless platforms. This study aims to examine the influence of QRIS (Quick Response Code Indonesian Standard) on consumer satisfaction within the framework of Sharia principles in Sanana District, North Maluku. In the digital transaction era, QRIS has emerged as a national standard for cashless payments, offering convenience, speed, and security. However, the extent to which QRIS affects consumer satisfaction, especially in semi-rural areas with limited digital literacy, remains underexplored. Using a quantitative method with a descriptive-associative approach, the study surveyed 30 consumers who had used QRIS in daily transactions. Data were collected through a structured questionnaire and analyzed using Structural Equation Modeling (SEM) via LISREL 8.80. The results show that QRIS has a positive and significant impact on consumer satisfaction (coefficient = 0.41; t-value = 9.66; p < 0.001). In addition, ease of use (0.35; t = 9.41) and transaction speed (0.38; t = 8.36) also significantly influence satisfaction. These findings suggest that QRIS is not only an effective digital payment solution but also aligns with Islamic financial ethics, promoting transparency, fairness, and efficiency.